The effect of male CEO masculinity face on earnings management: Evidence from Indonesia - Nur Fadjrih Asyik; Muchlis; Triyonowati; Rusdiyanto; Ignatia Martha Hendrati; Dian Anita Nuswantara; Suyanto (Cogent Economics & Finance, 2023)
AbstractThis study aims to prove the consistency of Agency Theory, Behavioral Consistency Theory and Upper Echelon Theory as a solution to explain the influence of male CEO masculinity on earnings management. This study uses a quantitative approach with a population and research sample using companies on the Indonesia Stock Exchange in 2016–2021. The study collected images of faces identified as male CEOs from data from the Indonesia Stock Exchange website and company websites and using Google searches. The data analysis method in this study uses Ordinary Least Square Regression, Fixed Effects, Random Effects, Robust by using Stata Software which is one of the regression solving procedures that has a high level of flexibility in research that connects theories, concepts and data that can be carried out on research variable. These findings explain that the higher the masculinity of the male CEO’s face has an impact on increasing earnings management, and vice versa, the lower the masculinity of the male CEO’s face has an impact on the decrease in earnings management. The empirical findings have implications for management as a policy maker regarding the face of male masculinity which has an impact on earnings management policies, so that these empirical findings can be used by corporate and government management. The empirical findings provide evidence in the field of behavioral accounting by looking at the face of male masculinity as determinant of company earnings management.